Current smoking is associated with extracranial carotid atherosclerotic stenosis but not with intracranial large artery disease - Ji, Ruijun (BMC Neurol, 2017)
BACKGROUND: Accumulating evidence has shown that cigarette smoking is an important risk factor for ischemic stroke. However, it is not clear about the potential mechanisms through which cigarette smoking affects stroke risk. In the study, we aimed to investigate the relationship between cigarette smoking and the occurrence of extracranial (ECAS) and intracranial atherosclerotic stenosis (ICAS). METHODS: We analyzed patients enrolled in the Chinese intracranial atherosclerosis (CICAS), which was a prospective, multicenter, hospital-based cohort study. Smoking status was classified into never, former and current smoking. For those patients with current smoking, data on time duration (year) and extent (the number of cigarette smoked per day) was recorded and pack year of smoking was calculated. ICAS was evaluated with 3-dimentional time-of-flight MRA and ECAS was evaluated with cervical ultrasonography or contrast-enhanced MRA. Multivariable Logistic regression was performed to identify the association between smoking status and the occurrence of ECAS and ICAS. RESULTS: A total of 2656 patients (92.7%) of acute ischemic stroke and 208 (7.3%) of transient ischemic attack were analyzed. The mean age was 61.9 ± 11.2 and 67.8% were male. There were 141 (4.9%) patients had only ECAS, 1074 (37.5%) had only ICAS, and 261 (9.1%) had both ECAS and ICAS. Current smoking was significantly associated with the occurrence of ECAS (adjusted OR = 1.47, 95% CI = 1.09–1.99, P < 0.01). In addition, with 1 year of smoking increment, the risk of ECAS increased by 1.1% (adjusted OR = 1.011; 95% CI = 1.003–1.019; P = 0.005); with one cigarette smoked per day increment, the risk of ECAS increased by 1.0% (adjusted OR = 1.010; 95% CI = 1.001–1.020; P = 0.03); and with one pack year of smoking increment, the risk of ECAS increased by 0.7% (adjusted OR = 1.007; 95% CI = 1.002–1.012; P < 0.01). However, no significant association was found between smoking status and the occurrence of ICAS. CONCLUSION: A dose–response relationship was identified between cigarette smoking and the occurrence of ECAS, but not ICAS. Further studies on molecular mechanisms were warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12883-017-0873-7) contains supplementary material, which is available to authorized users.